2020
DOI: 10.1093/mnras/stz3599
|View full text |Cite
|
Sign up to set email alerts
|

A robust, template-free approach to precise radial velocity extraction

Abstract: Doppler spectroscopy is a powerful tool for discovering and characterizing exoplanets. For decades, the standard approach to extracting radial velocities (RVs) has been to cross-correlate observed spectra with a weighted template mask. While still widely used, this approach is known to suffer numerous drawbacks, and so in recent years increasing attention has been paid to developing new and improved ways of extracting RVs. In this proof-of-concept paper we present a simple yet powerful approach to RV extractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 79 publications
0
46
0
Order By: Relevance
“…A methodology for correcting for these features is to consider spectral time series instead of individual spectra, as the former contain a richness of information far more extended than the latter. For example, this methodology shows its potential in the WOBBLE code (Bedell et al 2019), which is designed to remove telluric lines by performing a principal component analysis (PCA), or in the Gaussian process (GP) framework developed by Rajpaul et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…A methodology for correcting for these features is to consider spectral time series instead of individual spectra, as the former contain a richness of information far more extended than the latter. For example, this methodology shows its potential in the WOBBLE code (Bedell et al 2019), which is designed to remove telluric lines by performing a principal component analysis (PCA), or in the Gaussian process (GP) framework developed by Rajpaul et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Different methods consisting in a least-squares matching of a full spectrum template to the observations (Anglada-Escudé & Butler 2012;Astudillo-Defru et al 2015;Zechmeister et al 2018), rather than only using a selected set of absorption lines, have proven to work better for M-dwarf stars since they use more Doppler information contained in the spectrum. Recently, different methods have been proposed with the goal of improving RV extraction, such as using individual absorption lines (Dumusque 2018) or approaches using Gaussian processes (Rajpaul et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The second method we used to extract RVs was the GP-based method presented in Rajpaul et al (2020). In brief, GPs are used to model and align all pairs of spectra with each other; the pairwise RVs thus obtained are combined to produce differential stellar RVs, without constructing any template.…”
Section: Pairwise Gp Extractionmentioning
confidence: 99%
“…To avoid confusion from assigning multiple meanings to the Greek letter sigma, in this table we use 'SD' to denote the standard deviation of a given set of measurements, and 'error' to refer to the estimated 1σ error bars on measurements. Rajpaul et al (2020) showed that even a relatively crude implementation of the PWGP method, applied to an inactive star (where only modest if any improvements may have been expected compared to the DRS), resulted in RVs with precisions comparable to and rms scatter about 30 per cent lower than RVs extracted by the DRS and two other commonly-used codes, viz. HARPS-TERRA (Anglada-Escudé & Butler 2012) and SERVAL (Zechmeister et al 2018).…”
Section: Pairwise Gp Extractionmentioning
confidence: 99%
See 1 more Smart Citation